Changes in the Qualitative Composition of the milk of Holstein Cows During Summer Chronic Heat Stress - R Mylostyvyi; S Midyk; O Izhboldina; N Cherniy; V Kornienko (Jurnal Ilmu Ternak dan Veteriner, 2023)
Seasonal summer heat stress leads to significant economic losses, resulting in a drop in milk yield in dairy cows and a deterioration in milk quality. The purpose of this study was to determine the changes in some qualitative parameters of milk in Holstein cows during chronic heat stress on one of the largest commercial dairy farms Ukraine (50°49′14″ N, 31°49′23″ E). Five multiparous cows of medium lactation with a milk yield of about 30 kg per day were randomly selected into the reference (in the spring, at the end of May) and the experimental group (in the summer, at the end of August). Milk samples were taken from cows during the morning milking. Qualitative analysis of milk included the identification of milk solids-not-fat, density, mass fraction of lactose, fat, protein and minerals, as well as the freezing point, electrical conductivity and active acidity using ultrasonic method. Animals were kept in naturally ventilated barns. The total mixed single-type balanced diet consisting of corn silage and concentrates that the cows received remained unchanged. The sampling of milk from cows of the experimental group was preceded by a continuous 26-day hot period, during which the maximum daily values of the temperature and humidity index did not fall below 72 units. The results showed that in the milk of the animals of the experimental group there was a significant decrease in the content of milk solids-not-fat, the mass fraction of fat and protein (P0.05). The mass fraction of lactose and minerals tended to increase. It should be noted that the average daily milk yield of dairy cows in the herd in spring and summer was almost at the same level. In conclusion, the results of the study showed that high summer temperatures lead to a deterioration in the quality of milk in Holstein cows. Despite the decrease in milk density and freezing point, these figures met the requirements of the standard. Organoleptic indicators of milk, electrical conductivity and active acidity of milk did not change in hot weather, their value indicated the naturalness of milk. The mass fraction of milk fat, which undergoes the greatest change under the influence of seasonal heat stress, is one of the most valuable components of milk, which has a direct effect on nutritional value and purchase price of raw milk. Therefore, a further deeper study of the fatty acid composition of milk using the method of chromato-mass spectrometry will provide valuable data necessary to search for possible herd management strategies to maintain high milk quality under conditions of seasonal heat stress.